Managing Transition and Student Support Services for Ethnically Diverse College Students with Learning Disabilities - Sunday O. Obi (Educational Considerations, 2006)
Postsecondary transition for students with disabilities continues to be challenging.
Keywords: Students; learning disabilities; Diverse; college